The Chilean Economy During the 1810–1830s and Its Entry into the World Economy - Navarrete-Montalvo, J; Llorca-Jana, M (Blackwell Publishing Ltd, 2017)
This article discusses Chile s entry into the international economy, the performance of the national economy and institutional change during the 1810–1830s. It argues that the country consolidated a successful process of entry into the expanding world economy. GDP per capita was poor, but alternative indicators suggest a more optimistic picture (e.g., agricultural, copper and silver production increased, population grew and terms of trade improved). Furthermore, there were some positive institutional developments. All these changes made possible the sustained growth that took place from the 1830s and must be seen as more important than the growth record itself during the 1810–1820s. © 2016 The Authors. Bulletin of Latin American Research © 2016 Society for Latin American Studies. Published by John Wiley & Sons Ltd